Analisis Faktor-Faktor yang Mempengaruhi Kejadian Potentially Inappropriate Medications (PIMs) pada Pasien Geriatri Rawat Inap RSUD Dr. Soedomo Trenggalek - Widyaningrum, Esti Ambar; Rizky, Fara Nikhmatul; Irawati, Renny Nur Satya; Fajriyah, Shofiatul; Rilawati, Fentyana Dwi; Kurniawati, Evi; Lestari, Tri Puji (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Background: Geriatric patients are elderly patients with multiple diseases. Geriatric patients have more comorbidities and often receive polypharmacy prescriptions. PIMs have been identified in many elderly patients. One of the explicit criteria that can be used to identify the incidence of PIMs in geriatric patients is the Beers Criteria. Objective: To determine the frequency of PIMs and the factors that can influence the occurrence of PIMs based on the Beers Criteria in hospitalized geriatric patients at RSUD Dr. Soedomo Trenggalek. Method: This research uses a type of research with a retrospective observational analytical approach. The sampling technique used was purposive sampling with a total sample of 312 medical records. Inclusion criteria: age ≥ 65 years and exclusion: incomplete medical record data. Results: The most common characteristic profiles were male gender (62%), elderly (65-74 years) 69%, type of BPJS service (87%), main disease with the cardiovascular system (31%), number of diseases 2 (43%) and the number of drugs 6-10 drugs (50%). There was an incidence of PIMs of 78.53%. The factors gender, age, type of service, main diagnosis have a p value ≥ 0.05, while the number of diseases and medications have a p value ≤ 0.05. Conclusion: There is an incidence of PIMs in hospitalized geriatric patients of 78.53% with the number of diseases and number of medications influencing the incidence of PIMs in hospitalized geriatric patients.